2018
DOI: 10.1186/s12889-018-5210-6
|View full text |Cite
|
Sign up to set email alerts
|

The silent burden of stigmatisation: a qualitative study among Dutch people with a low socioeconomic position

Abstract: BackgroundIn-depth qualitative research into perceived socioeconomic position-related stigmatisation among people living at the lower end of our socioeconomic hierarchy is necessary for getting more insight in the possible downside of living in an increasingly meritocratic and individualistic society.MethodsSeventeen interviews were conducted among a group of Dutch people with a low socioeconomic position to examine their experiences with stigmatisation, how they coped with it and what they perceived as conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
5
18
0
Order By: Relevance
“…Poverty stigma – and negative public attitudes in particular - was further seen to affect individuals’ self-esteem and produce feelings of negative affect and shame. These findings are broadly consistent with previous qualitative research conducted in other parts of the UK (Chase and Walker, 2012) and internationally (Reutter et al, 2009; Simons et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Poverty stigma – and negative public attitudes in particular - was further seen to affect individuals’ self-esteem and produce feelings of negative affect and shame. These findings are broadly consistent with previous qualitative research conducted in other parts of the UK (Chase and Walker, 2012) and internationally (Reutter et al, 2009; Simons et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The stigma and discrimination were associated with poor education of women, poverty, differences in country of origin and due to disease such as HIV. The finding is consistent with a study on silent burden of stigmatization among Germanic ethnic group (Dutch women) in the Netherlands which found that women with low socio-economic status from a foreign country were discriminated [94]. In addition, our finding conforms with finding of secondary analysis on mistreatment of women during childbirth in healthcare facilities in developed countries where discrimination based on sociodemographic characteristics and medical conditions were found to impede RMC [95].…”
Section: ) Factors That Enhance Respectful Maternity Caresupporting
confidence: 92%
“…In addition to confusing messages about how much food was enough, the Virginia 365 intervention could have led to higher prevalence of food insecurity by exacerbating family feelings of stress and distress. Poverty carries stigma in US society, 27,28 and having school staff doubt a family's ability to provide sufficient food might have caused embarrassment, stress, and shame about the food situation. These feelings might have inherently harmed the well-being of children and families 3 and might have shaped responses to the food security assessment items, because some items ask specifically about feelings of worry and people appraise threats and challenges differently when they are experiencing stress.…”
Section: Messaging and Other Consequences Of Giving Free Foodmentioning
confidence: 99%